Answers

2015-12-09T05:24:57+08:00
You can eliminate one of the equation using multiplication of a certain number in one of the equation given above
2(7x-6y=12)
14x-12y=24
then you could now use subtraction
14x-12y=24 - 14x+y=24
14x-12y=24 + -14x-y=-24
-13y=0
y=0
then you can substitute the value of y in one of the original equation given
7x-6y=12
7x-6(0)=12
7x=12
x=12/7
you could use checking in the two equation
7(12/7)-6(0)=12
12-0=12
12=12 (check)

14(12/7)+0=24
2(12)+0=24
24+0=24
24=24 (check)
0